Home Healthcare Medication Safety risks among older adults with chronic diseases: a qualitative study - Tahereh Najafi Ghezeljeh; Zahra Amrollah Majdabadi Kohne; Mansoureh Ashghali Farahani; Forough Rafii; Sahar Keyvanloo Shahrestanaki (BMC Nursing)
Abstract Background Older adults receiving home care often face significant safety risks related to medication management due to their chronic diseases and complex health needs. Despite the increasing reliance on home healthcare services, the specific factors contributing to medication safety risks in this demographic remain inadequately explored. Objective/Aim This study aims to explore the key factors involved in medication safety risks among older adults with chronic diseases receiving home healthcare in Iran. Methods Qualitative research employing conventional content analysis was conducted using Graneheim and Lundman’s approach. was conducted in three home care centers in Tehran (Iran) from August 2020 to July 2022. Data were collected through semi-structured interviews with 7 nurses, 2 supervisors, 2 nursing assistants (experts in non-nursing careers), 1 home care inspector (expert of the Deputy of Treatment), and 3 family caregivers in home settings, along with four participatory observations and visual methods (narrative photography) focusing on medication safety challenges. The trustworthiness of the research was evaluated using Lincoln and Guba’s four criteria for qualitative studies. Findings Factors associated with medication safety risks were found to rely on its major components Patients’ attribution, Families’ characteristics, Home care centers’ condition, Health caregivers’ characteristics, and the Homes’ situations, where these factors all account for various medication safety risks. Indeed, a medication safety risk can be attributed to more than one of the factors associated with medication safety risk by participants at home. Conclusion As a result, the analysis of factors associated with medication safety risks highlights a complex interplay among various elements, including patients, families, home care centers, health caregivers, and the home environment. These interconnected factors are crucial for identifying the diverse medication safety challenges faced by participants in home settings. A comprehensive understanding of these dynamics is essential for improving medication safety protocols and enhancing health outcomes for this vulnerable population.